Pengaruh Teori Perilaku yang Direncanakan untuk Menyelidiki Peran Kepercayaan Dalam Keputusan Pembelian Konsumen Terkait dengan Rantai Pasok Makanan Pendek - Herli Qwen Sofana A; Ida Bagus Nyoman Udayana (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This study aims to explore the principles of behavioral theory towards customers, the influence of purchasing decisions, the role of trust in customers. This research is quantitative research using survey method. In taking the sample using purposive sampling technique. Collecting data using a questionnaire method that has been tested for validity and reliability. This study uses a sampling technique by distributing questionnaires for sampling as many people as possible so that they can be tested for validity and reliability. Behavioral theory shows that it is a potentially effective tool in planning the behavioral outcomes of union members in the workplace and the level of union identification considering decision making. defines behavioral theory as a social category that exemplifies the process of social behavior and its use affects the level of communication, interaction and cooperation between members. According to the theory of planned behavior trust has been neglected in retail. More details in retail marketing show aspects of customer trust are limited. The role of trustworthiness, such as reducing perceived problems and as a motivator of purchase satisfaction, plays an important role in customer trust in the product. Purchasing decisions refer to several organizations that carry out aspects of the decision-making process, until at the last moment the decision determines the point at which the decision is made. Decision making developed for business is used to describe how the company achieves purchasing synergies across its PCs. This approach can also be adopted in organizations with a high level of fragmentation in spending. Keywords: subjective norm, Trust towards the behavior (trust), Purchase decision (PD), customer.